Acute kidney injury following fatty liver ischemia-reperfusion injury: indirect protection by hepatic ferroptosis inhibition - Zhang, Wenjun; Rokop, Zachary; Li, Shan; Ferreria, Christina R.; Guo, Shunhua; Shou, Weinian; Dagher, Pierre; Sen, Chandan K.; Black, Sylvester; Kubal, Chandrashekhar (Frontiers in Physiology, 2025)
BackgroundThe association between hepatic ischemia-reperfusion injury (hIRI) in steatotic livers and subsequent acute kidney injury (AKI) is well established. Ferroptosis plays a critical role in fatty liver IRI. However, whether ferroptosis also contributes to secondary AKI following hIRI remains unclear.MethodshIRI was induced in mice fed either a high-fat, high-sucrose diet (HFD) or a normal diet (ND) to mimic the AKI commonly observed clinically after fatty liver transplantation. Kidney injury mechanisms were evaluated using histopathology, RNA sequencing, electron microscopy, and biochemical assays. Ferroptosis in the kidney was assessed by quantifying ACSL4, 4-hydroxynonenal (4-HNE), and AA-PE in homogenates and tissue sections. In parallel experiments, the lipid peroxidation inhibitor Liproxstatin-1 (Lip-1) was administered prior to hIRI to inhibit ferroptosis.ResultsAKI severity was markedly increased in HFD-fed mice compared to ND controls following hIRI. Histological, transcriptomic, and cytokine analyses revealed that apoptosis and inflammation were the primary mechanisms of kidney injury after HFD + hIRI. Kidney levels of ACSL4 and 4-HNE were not significantly elevated in either group after hIRI. Lip-1 treatment significantly reduced both liver injury and AKI in HFD-fed mice but showed no protective effect in ND-fed animals.ConclusionApoptosis and inflammation are the prominent kidney injury mechanisms involved in AKI following fatty liver IRI. Although ferroptosis may not be directly involved in the renal injury, anti-ferroptotic intervention mitigates AKI, supporting the concept that ferroptosis-mediated liver injury may serve as the primary upstream trigger in this context.